Obesity and the heart: cardiovascular magnetic resonance imaging evidence of the beneficial effects of bariatric surgery. - Rider, O; Byrne, J; Neubauer, S (2012)
Obesity is associated with cardiac hypertrophy and increased aortic stiffness, which are independent predictors of cardiovascular risk. In the setting of obesity, bariatric surgical weight loss has been shown to reduce mortality. We present a case showing that, in a severely obese individual without comorbidities, these cardiovascular responses to excess weight are reversible during weight loss over a period of 1 year.